The Relationship between Maternal Education and Incidence of Stunting at Boyolali Central Java - Wanda Youvada; Siti Arifah (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Stunting is still a serious problem for children in Indonesia, including in the Boyolali area, where the stunting rate reaches 20%. This condition occurs when children do not grow and develop properly due to chronic malnutrition, resulting in shorter height compared to their age and frequent infections during the critical first 1,000 days of life. Stunting according to the WHO Child Growth Standard is based on the length-for-age index (PB/U) or height-for-age (TB/U) with a limit (z-score) of less than -2 SD. Several factors contribute to stunting, one of the causes of high stunting is the mother's education level.This study aims to explore the relationship between maternal education and the incidence of stunting at the Sawit 1 Health Center, Boyolali Regency. The method used is a quantitative approach with a descriptive correlational design, and 135 respondents were selected through purposive random sampling based on certain inclusion and exclusion criteria. Data analysis conducted included univariate and bivariate analysis using Chi-Square using SPSS software version 20. The study was conducted from May to August 2024. The research findings revealed that 48 children (35.6%) were categorized as normal, 67 children (49.6%) were categorized as stunted, and 20 children (15.8%) were categorized as very short. Meanwhile, mothers of toddlers with elementary school education were 4 respondents (3.0%), mothers of toddlers with junior high school graduates were 37 respondents (27.4%), mothers of toddlers with high school graduates were 70 respondents (51.9%) and diploma and bachelor's graduates were 24 respondents (17.8%). It can be concluded that based on the results of the study, there is a significant relationship between the level of maternal education and the incidence of stunting at the Sawit 1 Health Center with a p value of 0.031 (p <0.05). Keywords : Incidence, Maternal Education Level, Stunting